Explaining the Behavioral Model of Auditors Based on Environmental Responsibility - Arab, Lela; Sotudeh, Reza; Haghparast, Abbasali; Hirad, Alireza (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: The present study aims to explain the behavioral model of auditors based on environmental responsibility. Methodology: The research employs a mixed-methods approach (qualitative and quantitative) and was conducted in 2024. In the qualitative phase, data were collected through interviews with 15 experts, achieving theoretical saturation using the grounded theory method. In the quantitative phase, the Friedman test was employed to rank the dimensions and components of the model. Additionally, the model’s validity was assessed by distributing a researcher-developed questionnaire among 384 experts, including faculty members, financial managers, and auditors from the Supreme Audit Court of the country, using SPSS software. Findings: The proposed model comprises three dimensions, 11 components, and 39 indicators. The dimensions of the behavioral model of auditors based on environmental responsibility include the organizational behavior dimension, which encompasses professional ethics, stakeholder consideration, environmental standards, and sustainable development; the social behavior dimension, which includes environmental culture, evaluation and monitoring, and sustainability reporting; and the individual behavior dimension, which consists of professional competence, individual attitudes and values, personal responsibility, and education and learning. Conclusion: Auditors must acquire the necessary skills to identify, evaluate, and report environmental issues. These skills include knowledge of environmental accounting and reporting across individual, organizational, and social behavioral dimensions, environmental risk analysis, and an understanding of relevant ethical principles.